Over-riding concerns: Developing safe relations in the high-risk interspecies sport of eventing - Thompson, K.; Nesci, C. (International Review for the Sociology of Sport, 2016)
Equestrian sports are unavoidably interspecies and undeniably dangerous. Whilst there has been qualitative research into the human-horse relationship, and quantitative research into horse riding, injury and risk, there remains a need to understand how risk perception and experience is subjectively implicated in, through and by the human-horse relationship, and vice versa. Doing so requires reconciling animal studies with risk theory. As a high-risk interspecies sport, eventing provides an exemplar case study for critiquing, extending and reconciling posthumanism and risk theorisation. This paper draws from interviews with 21 participants of the high-risk equestrian sport of eventing to explore the mutual benefits of using `risk` as a point d`entrée for analysing human-horse relations. Findings were largely consistent with three popular theories of voluntary risk-taking: edgework, flow and sensation-seeking. However, the involvement of an animal - the horse - stimulates a critical reconsideration of internal/external `control`; identifies a role for flow as risk mitigation/safety; and suggests that edge workers in high-risk interspecies sports do not just confront edges - they cross them. This paper thus distinguishes interspecies sports as a distinct and productive field of interdisciplinary research. It proposes further mixed-methods research that is required to more fully evaluate the usefulness of existing risk theory for understanding participant experiences of high-risk interspecies sports.